ICT Media Product Development In Islamic Historical Culture Learning - zuraida; Erli Tarona Putra; M. Fadli (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to analyze the development of ICT media products in Islamic Cultural History (ISH) learning and to describe the stages in developing these ICT media products. This study uses a literature review method (library research), namely by collecting and analyzing various relevant literature sources, such as scientific journals, books, articles, and previous research results related to the development of ICT-based learning media. The results of the study indicate that the use of ICT media in ISH learning provides a significant contribution to increasing learning interest, understanding of concepts, and active participation of students. In addition, ICT media is able to present teaching materials more interactively and contextually. The stages of ICT media product development in general include: identification of needs, design planning, content development, initial trials, evaluation, and product revision and refinement. Thus, the development of ICT media that is planned and based on student needs is very important to improve the quality of ISH learning as a whole.